Séance reflections - Werbner, Richard P.; International Centre for Contemporary Cultural Research; University of Manchester (Manchester, England : University of Manchester, 2004)
Njebe and Martha, a couple from Gaborone, Botswana, have tried various medical interventions to determine the reason why they remain childless. They decide to consult a charismatic diviner and healer in Njebe's birth village, Moremi. In reviewing portions of their filmed séances with ethnographer Richard Werbner, the couple are moved by the diviner's revelations about their intimate lives, but are puzzled by the diviner's rapid recital of highly ambiguous, archaic verse, his leading them in chants of call and response, and his preaching against Christianity and for restored communication with the ancestors, leaving the couple doubting the healing treatment.
Documentary.
Previously released as DVD.
Electronic reproduction.
This edition in English and Tswana with English subtitles.
Keywords: Ancestor worship -- Botswana; Healers -- Botswana; Healing -- Religious aspects; Spiritual healing -- Botswana; Traditional medicine -- Botswana; Nonfiction films; Ancestor worship; Healers; Healing -- Religious aspects; Spiritual healing; Traditional medicine; Botswana; Nonfiction films